What forces drive the dynamic interaction between regional housing prices?. Issue 3 (3rd July 2017) - Wu, Yun-Ling; Lu, Chien-Lin; Chen, Ming-Chi; Chu, Fang-Ni
ABSTRACT: This paper examines the dynamic interaction between regional housing prices in the United States. We use the copula method to explore the dependent distribution of housing prices in ten metropolitan statistical areas (MSAs) in three regions. The results generally show that changes in time-varying correlation result from different trends in regional housing prices. We regress housing price dynamic correlation on regional economic variables, finding that the economic co-movement mechanism determines the housing price correlation in the Western and Great Lakes regions, while the migration mechanism drives the housing price correlation in the Eastern region. We also find that economic co-movement is the main force driving the housing price correlation between regions.